Karakteristik Kelulusan Tepat Waktu Mahasiswa FMIPA UNP dengan Menggunakan Metode Classification and Regression Trees - Lilis Sulistiawati; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — This reaserch discussed about classification of timely graduation of college students. There are still a lot of students of Mathemathics and Natural Science Faculty of Universitas Negeri Padang who was overdue in Finishing their studies. This can affect the decline in study program accreditation or even reduce the university’s image. Therefore, this reaserch aims to determine the characteristic of students who graduate on time and who do not graduate on time based on variables of gender, school origin, scholarship, college entrance pathway, Grade Point Average (GPA), father’ occupation and mother’s occupation by using the Classification and regression Trees (CART) method. The population in this reaserch is the entire student of Mathemathics and Natural Science Faculty of Universitas Negeri Padang who graduated in 2018. The characteristics of college students who graduate on time is students who have a 3,51 – 4,00 GPA with a percentage of 75,2% and student who have a 2,00 – 3,50 GPA, received scholarship and came through the SBMPTN with a percentage 83,3%.Keywords — Characteristic of Graduation, Classification and Regression Trees (CART), Optimum Tree.